Math Trails: Meaningful Mathematics Outside the Classroom With Pre-Service Teachers - Isabel Vale; Ana Barbosa (European Teacher Education Network, 2016)
This paper presents a study about the potential of the construction of math trails as a non-formal context in the teaching and learning of mathematics. This research is of qualitative nature and was developed with future teachers of basic education. It can be said that these future teachers showed a more positive attitude towards mathematics, broadening their perspective about the connections that can be established between mathematics and everyday life. Results suggest as well that despite the construction of the trail not being easy, as well as the process of designing the tasks that focused mainly on geometry, it was possible to identify traces of originality and involvement on the part of the participants.